Предмет: Алгебра,
автор: xuda
Решить (2x+3)^2=(x+4)^2
Ответы
Автор ответа:
0
(2x + 3)^2 - (x + 4)^2 = 0
(2x + 3 - (x + 4)) (2x + 3 + x + 4) = 0
(2x + 3 - x - 4)(2x + 3 + x + 4) = 0
(x - 1)(3x + 7) = 0
1) x - 1 = 0
x = 1;
2) 3x + 7 = 0
3x = - 7
x = - 7/3
(2x + 3 - (x + 4)) (2x + 3 + x + 4) = 0
(2x + 3 - x - 4)(2x + 3 + x + 4) = 0
(x - 1)(3x + 7) = 0
1) x - 1 = 0
x = 1;
2) 3x + 7 = 0
3x = - 7
x = - 7/3
Похожие вопросы
Предмет: Химия,
автор: Бег123
Предмет: Математика,
автор: arik83365
Предмет: Химия,
автор: Бег123
Предмет: Литература,
автор: ajara1982
Предмет: Математика,
автор: Saanastya